Addressing Transgender Erasure in HIV Clinical Trials: The Scorecard for Transgender and Gender-Diverse Inclusion. - Minalga, Brian; Feuer, Cindra (American Journal of Public Health, 2025)
We sought to offer a structured framework for evaluating transgender and gender-diverse (TGD) inclusion in HIV clinical trials, with actionable criteria for trial design and conduct, and to quantify and characterize TGD inclusion in pivotal HIV studies as supporting evidence of the need for this framework. We devised a tool (scorecard) consisting of 14 scoreable indicators for TGD-responsive HIV research with input from global TGD communities. We tested the scorecard in a cross-sectional review of 41 randomized controlled HIV biomedical efficacy trials to measure TGD responsiveness. Studies were selected to represent the spectrum of groundbreaking HIV therapeutic and prevention studies enrolling participants in countries around the world from 1991 to 2023. We found that TGD individuals represent a reported 2532 (1.4%) of 178 893 participants in the selected HIV clinical trials. Scorecard indicators reveal a dearth of HIV research responsive to the needs of TGD communities. The lack of TGD representation in HIV clinical trials indicates a historical erasure of TGD communities with potential public health consequences. The scorecard might guide future HIV research to be more responsive to the needs of TGD people.